On luck and significance. - Hill, Jesse (Synthese, 2022)
It is often assumed that all lucky events are significant. The thought is that a chancy event such as winning the lottery is lucky for you in part because it affects your interests or well-being. But whether you win an Absurdist Raffle in which there are no prizes, is, intuitively, not a matter of luck. This is because this event—even if chancy—is not significant for any subject. However, a few philosophers have recently claimed not only that luck does not necessarily involve a significance condition but that we should not view luck involving claims in terms of significance. After reviewing the literature on this topic, I argue that lucky events are significant. A significance condition is necessary to distinguish between different kinds of luck: practical, epistemic, and moral. All lucky events are significant and chancy, but they can be significant for subjects in different ways. For example, an event is epistemically lucky for you if it is epistemically significant and chancy, but such events need not affect your practical interests or moral standing. Furthermore, I argue that events that are chancy but not significant should be thought of in terms of chance and not luck.